Structure of the anal canal and distal rectum in Wistar rats - O. A. Goldberg (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The conducted research relates to the structure of anal canal and distal rectum of Wistar rats. This structure is of interest in terms of comparative anatomy and as an object of experimental model in pathology. We studies female rats aged 6-10 months, weighing 200-300 g. Light microscopy of specimens was performed with the system microscope LEICA DM2000 (Germany). The study findings revealed that the anal canal is lined with multilayered epithelium on the connective tissue, in distal part ofwhich are buried hairfollicles, adipose glands and rudiments of perspiratory glands. Passage of anal canal into the skin with high density of hairfollicles with adipose glands is a white line. Intrinsic sphincter is identified by thickening of circular layer of the intestine. External sphincter is presented by separate complexes of skeletal muscles fibers, placed exteriorly and inferiorly from the anal canal muscle layer under the hypoderma. We did not detect the Parks' ligament as a separate structure. This means that the function of this part of the intestine in rats and that one of a human are not completely consistent.